Dietary fibre in food and protection against colorectal cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC): an observational study. - Bingham, SA; Day, N; Luben, R; Ferrari, P; Slimani, N; Norat, T; Clavel-Chapelon, F; Kesse, E; Nieters, A; Boeing, H; Tjønneland, A; Overvad, K; et al. (2003)
BACKGROUND: Dietary fibre is thought to protect against colorectal cancer but this view has been challenged by recent prospective and intervention studies that showed no protective effect. METHODS: We prospectively examined the association between dietary fibre intake and incidence of colorectal cancer in 519978 individuals aged 25-70 years taking part in the EPIC study, recruited from ten European countries. Participants completed a dietary questionnaire in 1992-98 and were followed up for cancer incidence. Relative risk estimates were obtained from fibre intake, categorised by sex-specific, cohort-wide quintiles, and from linear models relating the hazard ratio to fibre intake expressed as a continuous variable. FINDINGS: Follow-up consisted of 1939011 person-years, and data for 1065 reported cases of colorectal cancer were included in the analysis. Dietary fibre in foods was inversely related to incidence of large bowel cancer (adjusted relative risk 0.75 [95% CI 0.59-0.95] for the highest versus lowest quintile of intake), the protective effect being greatest for the left side of the colon, and least for the rectum. After calibration with more detailed dietary data, the adjusted relative risk for the highest versus lowest quintile of fibre from food intake was 0.58 (0.41-0.85). No food source of fibre was significantly more protective than others, and non-food supplement sources of fibre were not investigated. INTERPRETATION: In populations with low average intake of dietary fibre, an approximate doubling of total fibre intake from foods could reduce the risk of colorectal cancer by 40%.